Biocontrol of root-knot nematode, Meloidogyne incognita damaging queen palm, Livistona rotundifolia using Trichoderma species. - Jegathambigai, V.; Karunaratne, M.D.; Svinningen, A.; Mikunthan, G. (My University, 2008)
Livistona rotundifolia is a widely grown queen palm in all the net houses of floriculture industries in Sri Lanka. It is grown to an extent of 10,000 mZ in Green Farms Ltd, Marawilla under shade net house. Root knot nematode is one among the key pests of queen palms and causes heavy loss in the queen palm industry. Queen palm is grown in a coir based compost media under sprinkler irrigation. Management of nematodes using chemicals is impractical due the non availability and selectivity of the nematicides available in the market. This study attempted to evaluate the efficacy of Trichoderma species to control root knot nematode, Meloidogyne incognita that damage L. rotundifolia and caused heavy loss at Green Farms Ltd, Marawilla. Experiments were conducted using organic amendments with T. viride + T. harzianum (1 x 10(10) cfu/ml) to control the nematodes. Carbofuran (3%) (2.5 g/750 ml pot with organic amendments), the only available pesticide with nematicidal property, was used as a standard check. Queen palm naturally infected with M. incognita was treated with Trichoderma species and the effect was compared with the carbofuran treatment. Standard procedures were adopted to count the nematodes in the pre and post treated queen palm plots. The results revealed that the application of mixture of T. viride and T. harzianum at 1 x 10(10) cfu/ml significantly reduced the nematode populations in the media and number of galls in the palms compare to Carbofuran treated palms. Eggs and juveniles of M. incognita were found infected with Trichoderma species under the in-vitro conditions. The population of M. incognita was started declining significantly 3 weeks after the first application of Trichoderma species in the field. The response was apparent in the palms treated with mixture of Trichoderma species and recovered within 3 months as a healthy and quality product with export standards.